2020
DOI: 10.1016/j.molp.2019.11.004
|View full text |Cite
|
Sign up to set email alerts
|

The Features and Regulation of Co-transcriptional Splicing in Arabidopsis

Abstract: Precursor mRNA (pre-mRNA) splicing is essential for gene expression in most eukaryotic organisms. Previous studies from mammals, Drosophila, and yeast show that the majority of splicing events occurs co-transcriptionally. In plants, however, the features of co-transcriptional splicing (CTS) and its regulation still remain largely unknown. Here, we used chromatin-bound RNA sequencing to study CTS in Arabidopsis thaliana. We found that CTS is widespread in Arabidopsis seedlings, with a large proportion of altern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
79
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(87 citation statements)
references
References 85 publications
5
79
0
Order By: Relevance
“…We propose that these changes in nucleosome occupancy may provide the basic definition to exons and introns to coordinate RNAPII processivity. However, it is apparent that the splicing process is also fine‐tuned by various trans ‐regulatory factors and histone modifications under variable growth and stress conditions (Kindgren et al ., 2019; Zhu et al ., 2020). Our data support this notion, and it is likely that higher nucleosome occupancy may regulate RNAPII accumulation around splice sites and enable SF recruitment to facilitate and/or modulate splicing variation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We propose that these changes in nucleosome occupancy may provide the basic definition to exons and introns to coordinate RNAPII processivity. However, it is apparent that the splicing process is also fine‐tuned by various trans ‐regulatory factors and histone modifications under variable growth and stress conditions (Kindgren et al ., 2019; Zhu et al ., 2020). Our data support this notion, and it is likely that higher nucleosome occupancy may regulate RNAPII accumulation around splice sites and enable SF recruitment to facilitate and/or modulate splicing variation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence shows that alternative splicing (AS) regulation is a key gene regulatory mechanism in plants (Calixto et al ., 2018; Filichkin et al ., 2018; Jabre et al ., 2019). In plants and animals, AS is regulated co‐transcriptionally (Brody et al ., 2011; Tilgner et al ., 2012; Li et al ., 2020; Zhu et al ., 2020). RNA polymerase II (RNAPII) speed during transcription may be affected by the chromatin state that in turn determines AS outcomes (Alexander et al ., 2010; Ullah et al ., 2018; Zhu et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, CTS was found to be the predominant mode of splicing in different species, including humans, Drosophila and budding yeast (Ameur et al, 2011;Khodor et al, 2011;Oesterreich et al, 2016). Recently, it was found that this also occurs in A. thaliana (Li et al, 2020;Zhu et al, 2020). These findings suggest that for circadian genes, constitutive splicing would also occur in a circadian fashion, as it would occur co-transcriptionally.…”
Section: Discussionmentioning
confidence: 99%
“…This occurs more efficiently for introns of protein-coding genes, and less efficiently for introns with AS sites (Li et al, 2020). Additionally, it has been found that CTS is independent of gene length, but rather correlates with gene expression level, chromatin landscape, and total number of introns and exons of the gene in question (Zhu et al, 2020). Through this process, different functional mRNAs can arise from the transcription of the same gene, ultimately expanding the repertoire of protein products that can be encoded by a single gene (Kornblihtt et al, 2013;Saldi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%